Toothpaste Consumption: Implications for Health and Sustainability in Oral Care - Nicita, Fabiana; D'Amico, Cesare; Minervini, Giuseppe; Cervino, Gabriele; Fiorillo, Luca (European Journal of General Dentistry, 2023)
Objective Toothpaste is a crucial component of daily oral hygiene routines and is significant in maintaining oral health. This study aimed to assess the amount of toothpaste consumed during tooth brushing and investigate the influence of toothbrush type on toothpaste consumption.Materials and Methods Ten volunteer students of dentistry who regularly practiced oral hygiene at home were enrolled. Participants used a 15-mL tube of toothpaste with manual and electric toothbrushes and the amount consumed was recorded three times daily.Statistical Analysis Variance analysis for repeated measures was applied for differences within groups for toothbrush types while the t-test was carried out to compare the mean quantities between groups. Statistical significance was set at p < 0.05.Results The findings revealed no significant difference in toothpaste consumption across different time intervals for both manual and electric toothbrushes. However, a significant difference in toothpaste consumption was observed when comparing toothbrush types. Participants using electric toothbrushes consumed less toothpaste compared to those using manual toothbrushes.Conclusion The observed differences in toothpaste consumption highlight the importance of considering toothbrush type when promoting appropriate usage. With their advanced brushing mechanisms, electric toothbrushes may enhance cleaning efficiency and reduce the need for a large amount of toothpaste. Reducing toothpaste consumption benefits oral health and contributes to environmental sustainability. It minimizes packaging waste, conserves energy and resources, promotes water conservation, preserves ecosystems, and encourages a culture of ecological responsibility. By embracing a more conscious approach to toothpaste usage, individuals can contribute to a greener and more sustainable future.
Keywords: oral hygiene; toothpaste consumption; sustainability; oral care